Dynamic Material Model Parameters for Laminated Glass by Analytical Approach and its Simulation as per EN 1063. (2018) - Thakur, Nitin; Bharj, Rabinder Singh; Kumar, Pramod
Abstract: Laminated glass is finding increasing applications in defence and architecture due to safety and its aesthetic value. In the present research, some of the parameters of exponent form of Drucker-Prager model, EOS, and Ductile Damage are determined for soda-lime glass using analytical approach and the experimental work by Bharj and Kumar have been validated with the help of numerical simulations using ABAQUS explicit finite element code by incorporating the determined material parameters. In this research paper, it was shown that the impact energy absorbed by the laminated glass increased with the increase in overall thickness of the target and the position of interfacial layer did not affect the impact energy absorbed by the laminated glass, provided that the conditions should be same. The numerical work was in close agreement with the experimental work and thus is beneficial in saving a lot of time, material and effort